An Optimist Pleads Guilty - Mickle, Joe J. (Tufts Archival Research Center, 2006)
Joe Mickle, President of the Centenary College of Louisiana, describes his enthusiasm for life and his gratitude for the sacrifices of previous generations, and states his belief that gratitude is linked to action, i.e., that an individual who is grateful lives to please God.